How Much Does Honesty Cost? Small Bonuses Can Motivate Ethical Behavior - Wang, Long; Murnighan, J. Keith (Management Science, 2017)
Although people generally try to avoid lying, the lure of potential monetary payoffs often leads to unethical behavior. The current research investigates whether small monetary rewards for honesty help people resist the temptations of larger incentives or whether they backfire and lead to even more dishonesty. Four experiments address these issues. Experiment 1 shows that a $1 bonus led people to act more honestly when they could have lied to obtain $4; an identical bonus, however, did not increase dishonesty. Experiment 2 uses a different context and again shows that a $1 bonus led people to act more honestly; it also finds no evidence that this small payoff crowded out subsequent altruistic behavior. Experiment 3 shows that a $1 bonus increased people’s honesty even when the payoffs for lying increased to $8, $12, and $16, but not when the payoff for lying increased to $20. Experiment 4 finds that smaller bonuses for honesty still had an impact, although it tended to be somewhat weaker. In addition, compared with no bonus, the combined effect of several small monetary bonuses (1 dollar, 75 cents, 50 cents, and 25 cents) marginally reduced lying. Data are available at http://dx.doi.org/10.1287/mnsc.2016.2480 . This paper was accepted by Uri Gneezy, behavioral economics.